2020
DOI: 10.1038/s41467-020-16050-w
|View full text |Cite
|
Sign up to set email alerts
|

Naked mole-rat very-high-molecular-mass hyaluronan exhibits superior cytoprotective properties

Abstract: Naked mole-rat (NMR), the longest-living rodent, produces very-high-molecular-mass hyaluronan (vHMM-HA), compared to other mammalian species. However, it is unclear if exceptional polymer length of vHMM-HA is important for longevity. Here, we show that vHMM-HA (>6.1 MDa) has superior cytoprotective properties compared to the shorter HMM-HA. It protects not only NMR cells, but also mouse and human cells from stressinduced cell-cycle arrest and cell death in a polymer length-dependent manner. The cytoprotective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 49 publications
0
58
1
Order By: Relevance
“…It has previously been suggested that HA of different MW may affect the same receptors differently; however, recent study refutes this theory [ 23 ]. On the other hand, it has been shown that HA of very high molecular weight (6000 kDa) produced by naked mole-rat suppresses the signaling of CD44, which results in altered expression of a subset of p53 target genes, thereby suggesting that HMWHA has the properties of a cytoprotective molecule [ 24 ], but there are differences in the genes regulated by p53 between different species so this investigation is restricted to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been suggested that HA of different MW may affect the same receptors differently; however, recent study refutes this theory [ 23 ]. On the other hand, it has been shown that HA of very high molecular weight (6000 kDa) produced by naked mole-rat suppresses the signaling of CD44, which results in altered expression of a subset of p53 target genes, thereby suggesting that HMWHA has the properties of a cytoprotective molecule [ 24 ], but there are differences in the genes regulated by p53 between different species so this investigation is restricted to human cells.…”
Section: Introductionmentioning
confidence: 99%
“…S6C). Masson’s trichrome staining for collagenous connective tissue fibers revealed no difference between the 2 groups just like hyaluronic acid, a linear polysaccharide of the extracellular matrix contributing to contact inhibition and cell proliferation( 41 ) (Fig. 5 D-E).…”
Section: Resultsmentioning
confidence: 97%
“…Reduced senescence in NMR joints may be another factor protecting from OA. As HMW-HA has cytoprotective properties (Takasugi et al, 2020), it may be acting to attenuate senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced senescence in NMR joints may be another factor protecting from OA. As HMW‐HA has cytoprotective properties (Takasugi et al, 2020), it may be acting to attenuate senescence. Finally, there may be systemic factors contributing to NMR OA resistance, such as lower levels of inflammatory response, as high molecular weight HA downregulates inflammation (Petrey & de la Motte, 2014).…”
Section: Discussionmentioning
confidence: 99%